2011
DOI: 10.1055/s-0031-1293515
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Diagnosis and Outcome of Fetuses with Double-Inlet Left Ventricle

Abstract: The aim of this study is to characterize the in utero presentation of the subtype of double-inlet left ventricle (DILV), a rare congenital heart disease, and assess the postnatal outcome. We retrospectively studied fetuses diagnosed prenatally with DILV between 2007 and 2011. We reviewed the prenatal and postnatal echocardiograms, clinical presentations, karyotypes, and the postnatal outcomes. There were eight fetuses diagnosed with DILV with L-transposition of the great vessels (S, L, L). Mean gestational age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…We found only two studies that included data on CHB in patients with univentricular L‐looped hearts. These studies reported an incidence of CHB of 19% and 25% . The context of CHB (spontaneous vs. perioperative) was not specified in these studies .…”
Section: Discussionmentioning
confidence: 98%
“…We found only two studies that included data on CHB in patients with univentricular L‐looped hearts. These studies reported an incidence of CHB of 19% and 25% . The context of CHB (spontaneous vs. perioperative) was not specified in these studies .…”
Section: Discussionmentioning
confidence: 98%
“…For the purposes of extrapolating percentages, 40,000 CHDs per year are estimated . Repeat surgeries affect an estimated 6700–8700 children every year in the US, and cost the healthcare system hundreds of millions of dollars . The primary clinical application for an expandable conduit is most likely a nonvalved conduit.…”
Section: Discussionmentioning
confidence: 99%
“…The primary clinical application for an expandable conduit is most likely a nonvalved conduit. A total patient population for SV CHD is between 2700–3800 in the US per year . COA is estimated to be present in 7% of children with CHDs, or 2800 patients, although only a minority requires an interposition graft .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coarctation of the aorta can be a progressive lesion in utero with relative worsening of the distal arch hypoplasia in later gestation, due to continual decrease in the amount of blood flow traversing the isthmus as pregnancy progresses 4. Quantitative distal aortic arch hypoplasia and ventricular and great artery size discrepancy have been observed and may facilitate the diagnosis of coarctation of the aorta during serial echocardiographic evaluation 5. Although distinct criteria have been established for the diagnosis of LVNC after birth, criteria for diagnosis in the fetus have not been established 3.…”
Section: Discussionmentioning
confidence: 99%